2022
DOI: 10.15575/jt.v5i1.16085
|View full text |Cite
|
Sign up to set email alerts
|

Causes and Impacts of Early Marriage: A Phenomenological Study in the Cimarel Hamlet Community, West Bandung Regency

Abstract: Penelitian ini bertujuan untuk menginterpretasikan persepsi pernikahan dini, penyatuan dua insan yang salah satu atau keduanya berusia di bawah 18 tahun melalui pendekatan fenomenologis. Metode penelitian yang digunakan adalah kualitatif, dengan pengumpulan data melalui observasi disertai wawancara mendalam yang didukung dengan pendekatan analisis dokumentasi induktif. Hasil penelitian menunjukkan bahwa masyarakat di Dusun Cimarel, Bandung Barat memandang perlunya pernikahan dini pada anak perempuan berusia 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
1
Order By: Relevance
“…The role of the level of education is related to the family's understanding of family life. This is supported by Ginting, who found that the lower the family's education, the more often teenage marriages and teenage pregnancies are found [26]. The results of this study are not in line with research conducted by Pohan; there is a relationship between knowledge and early marriage in young women [22].…”
Section: The Relationship Between Knowledge and Early Marriage In You...contrasting
confidence: 85%
“…The role of the level of education is related to the family's understanding of family life. This is supported by Ginting, who found that the lower the family's education, the more often teenage marriages and teenage pregnancies are found [26]. The results of this study are not in line with research conducted by Pohan; there is a relationship between knowledge and early marriage in young women [22].…”
Section: The Relationship Between Knowledge and Early Marriage In You...contrasting
confidence: 85%
“…The community in Cimarel Hamlet, West Bandung, saw the need for early marriage for girls aged 15 to 16 years as matchmaking, avoiding the social stigmas of adultery and pregnancies outside of marriage, and as an economical solution for parents to shift their responsibilities. Was based on recent studies about early marriage in Bandung with different locations(Rahim et al, 2022). The risk of early marriage increases with high exposure to information, negative attitude, and strong intention.…”
mentioning
confidence: 99%